Formulation and evaluation of erythropoietin-alginate microspheres at different amount of drug - Hariyadi, Dewi; Hendradi, Esti; Lailiyah, Khoirotul (Pharmaciana, 2018)
This research formulate erythropoietin-alginate microspheres and to evaluate characteristics of erythropoietin-alginate microspheres at different amount of drug using aerosolization. Amount of erythropoietin are 10.000 IU (F1); 20.000 IU (F2); 60.000 IU (F3). The mixture of erythropoietin-alginate was sprayed into CaCl2 and was stirred at 1000 rpm for 30 minutes. Formulas resulted spherical shape of microspheres. The size of microspheres was 2.77 µm for F1; 3.89 µm for F2; and 4.42 µm for F3. The results of swelling index showed that swelling index of microspheres increased by increasing the concentration of erythropoietin. The results were in accordance with the size of the microspheres that increased with increasing concentration of drug. The yields of microspheres obtained were respectively 91.92%; 87.53%; 86.50% for F1, F2 and F3. It can be concluded that the particle size of microspheres, swelling index increased by increasing concentration of erythropoietin. In contrast, yield of microspheres decreased by increasing drug concentration. In conclusion, formula of microspheres were potential in terms of characteristics and may recommend for further in vivo study.